ANALISIS PENGARUH KUALITAS PRODUK, KESADARAN MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL HONDA MOBILIO DI KOTA SEMARANG - Erdiana, Nila; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2015)
This study was motivated by competition and business threats that occur in the automotiveindustry in particular on products Honda Mobilio. The decline in the value of the index in Table Honda car sales indicate there is a problem in product purchasing decisions Honda Mobilio. This study aims to analyze and examine the elements that comprise the purchase decision of the product quality, brand awareness, and the price of the product purchase decisions Honda Mobilio.Research data retrieval is done through questionnaires to 100 respondents Honda Mobilio car users in the city of Semarang is obtained using the technique accidental sampling and purposive sampling. Then the analysis of data obtained both qualitatively and quantitatively. Qualitative analysis is the interpretation of the data obtained in the field and analysis of open answers given by the respondents, whereas quantitative analysis include: validity, reliability, classic assumption test, multiple linear regression, hypothesis testing via t test and F test, and coefficient of determination(R2).Data - data that has met the validity, reliability, and classical assumption, processed with SPSS (Statistical Package for Social Science) for Windows 15, resulting in a regression equation as follows: Y = 0,240 X1 + 0,589 X2 + 0,376 X3Where hypothesis testing using t test showed that the three independent variables, namely the quality of the product (X1), brand awareness (X2), and the price (X3) significant positive effect on the purchase decision (Y).